2021
DOI: 10.1088/1757-899x/1147/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diameter of the cored wires on abrasive wear resistance of arc sprayed coatings

Abstract: To obtain wear-resistant coatings, the cored wires (CW) with a diameter of 1.6…1.8 mm as electrode materials are mainly used. Using the large-diameter CW enable significantly increase the filling of their shells with powder charges and, as a consequence, to essentially raise the content of alloying elements in the coating structure. The model cored wires of two basic alloying systems Fe – Cr – C and Fe – Cr – B with a diameter of 1.6 and 2.4 mm used for spraying. Three types of the cored wires (namely 50CrNi2B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Pokhmurska et al [ 31 ] showed that Cr 3 C 2 dispersed in the solid solution can effectively enhance the hardness of the coating. Figure 5 compares the average surface and cross-sectional hardness values of the cladding layer, revealing that the hardness of the composite coating generally increases with the increase in Cr 3 C 2 content, reaching a maximum of 825.4 HV3.…”
Section: Resultsmentioning
confidence: 99%
“…Pokhmurska et al [ 31 ] showed that Cr 3 C 2 dispersed in the solid solution can effectively enhance the hardness of the coating. Figure 5 compares the average surface and cross-sectional hardness values of the cladding layer, revealing that the hardness of the composite coating generally increases with the increase in Cr 3 C 2 content, reaching a maximum of 825.4 HV3.…”
Section: Resultsmentioning
confidence: 99%
“…The workability of ASCs is largely determined by their hardness, cohesive strength and level of residual stresses. The porosity of coatings also affects their mechanical characteristics [28]. The deposition modes of coating (current values, distance to the sprayed surface) and the chemical composition of the CW charge have little effect on their porosity.…”
Section: Resultsmentioning
confidence: 99%
“…34 V. CW was sprayed with a flow of compressed air at a pressure of 0.6 MPa from a distance of 150 mm. On the example of a number of CWs with fundamentally different charge compositions, the spraying mode of coatings was optimized [28]. This mode was actually used in this article.…”
Section: Depositionmentioning
confidence: 99%